A Network Pharmacology of Lemongrass (Cymbopogon citratus) on COVID-19 Cases - Saputro, Dominyda Vebrianto; Jamil, Ahmad Shobrun; Muchlisin, M Artabah; Almuhtarihan, Irsan Fahmi (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 3 (2023): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v3i0.2471, 2023)
Various ways and treatment efforts are carried out to avoid the severe impact of COVID-19 cases, one of which is using plants as natural immunomodulatory agents. One of the plants that is proven to act as a natural immunomodulator is lemongrass ( Cymbopogon citratus ). This study aimed to determine the protein tissue associated with the body's immune system activated by C. citratus . The secondary metabolites of C. citratus were identified using the KNApSAck and Dr. Duke databases. Target proteins associated with plant-secondary metabolite compounds from the SwissTargetPrediction database and immunomodulatory-associated target proteins were obtained from the GeneCards database. The intersected proteins were put into StringDB and analyzed using KEGG to obtain network pharmacology. 98 secondary metabolite compounds of C. citratus were obtained from the database. Proteins associated with C. citratus contain 1096 compounds, and those related to immunomodulators contain 1380 proteins. The intersection results obtained 244 proteins predicted to interact with C. citratus and are related to immunomodulators. From the results of KEGG analysis, five pathways related to C. citratus were obtained, namely PD-L1 expression and PD-1 checkpoint pathway in cancer, Fc epsilon RI signaling pathway, Th17 cell differentiation, T cell receptor signaling pathway, and IL-17 signaling pathway. MAPK 1, MAPK 3, and MAPK 14 proteins are predicted to be in all five related pathways, and Mol 13 compounds are predicted to be able to interact with these three proteins. Thus, it can be concluded that the compound Mol 13 is the compound that plays the most role in acting as an immunomodulator in C. citratus.